2018
DOI: 10.1002/aoc.4266
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoparticle‐tethered Schiff base–palladium(II): Highly active and reusable heterogeneous catalyst for Suzuki–Miyaura cross‐coupling and reduction of nitroarenes in aqueous medium at room temperature

Abstract: As a continuation of our efforts to develop new heterogeneous nanomagnetic catalysts for greener reactions, we identified a Schiff base-palladium(II) complex anchored on magnetic nanoparticles (SB-Pd@MNPs) as a highly active nanomagnetic catalyst for Suzuki-Miyaura cross-coupling reactions between phenylboronic acid and aryl halides and for the reduction of nitroarenes using sodium borohydride in an aqueous medium at room temperature. The SB-Pd@MNPs nanomagnetic catalyst shows notable advantages such as simpli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 75 publications
1
37
0
Order By: Relevance
“…In the second stage, up to 11% weight loss of the MNPs‐MIC‐Pd nanomagnetic catalyst can be observed from the range of 150 °C to 730 °C and this is because of the decomposition of organic moiety immobilized on surface of MNPs. Moreover, TGA result confirms the successful immobilization of organic moiety on the surface of MNPs and also reveals that MNPs‐MIC‐Pd nanomagnetic catalyst is stable up to 230 °C which helps to carry out the cross‐coupling reactions even at higher temperature …”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations
“…In the second stage, up to 11% weight loss of the MNPs‐MIC‐Pd nanomagnetic catalyst can be observed from the range of 150 °C to 730 °C and this is because of the decomposition of organic moiety immobilized on surface of MNPs. Moreover, TGA result confirms the successful immobilization of organic moiety on the surface of MNPs and also reveals that MNPs‐MIC‐Pd nanomagnetic catalyst is stable up to 230 °C which helps to carry out the cross‐coupling reactions even at higher temperature …”
Section: Resultsmentioning
confidence: 53%
“…Figure shows the FT‐IR spectra of MNPs‐MIC‐Pd nanomagnetic catalyst and recycled MNPs‐MIC‐Pd nanomagnetic catalyst. FT‐IR spectra of ten times recycled MNPs‐MIC‐Pd nanomagnetic catalyst from Suzuki‐Miyaura cross‐coupling (Figure b) and five times recycled MNPs‐MIC‐Pd nanomagnetic catalyst from Mizoroki‐Heck cross‐coupling reactions (Figure c) confirmed that MNPs‐MIC‐Pd nanomagnetic catalyst was unaltered and remained almost same even after ten cycles in Suzuki‐Miyaura and five cycles in Mizoroki‐Heck cross‐coupling reactions …”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…To resolve these drawbacks, homogeneous metal salen complexes are converted to heterogeneous counterpart. Several insoluble solid supports such as zeolites, polymer supports, mesoporous materials, clays, organic polymer‐inorganic hybrid materials, SBA‐15, MCM‐41 and activated silica were employed for immobilizing of homogeneous metal‐salen complexes …”
Section: Introductionmentioning
confidence: 99%